A randomized-controlled trial of heart rate variability biofeedback for psychotic symptoms - Clamor, Annika; Koenig, Julian; Thayer, Julian F.; Lincoln, Tania M. (Behaviour research and therapy, 2016)
Arousal and the way it is coped with are relevant to the emergence of psychotic symptoms. Heart rate variability (HRV) stems from autonomic responses to environmental demands such as stress and is an index of physiological arousal, adaptability, and homeostatic reflexes forming autonomic balance. A randomized-controlled between-subjects trial that compared HRV-biofeedback (BF) to an active relaxation and to a waiting control condition was conducted in a sample with attenuated subclinical psychotic symptoms (N = 84). A 20-min intervention was preceded and followed by repeated assessments of stress responses. Change scores of the post-stress periods were analyzed using ANOVAs for HRV, subjective stress, perceived control, and state paranoia. As expected, BF participants showed greater improvements in perceived control than waiting controls (p = 0.006). However, no group differences occurred in HRV, paranoid symptoms or subjective stress. In exploratory analyses in a subset of participants who were breathing per protocol, the expected effects were found for total HRV and state paranoia. Thus, this trial of HRV-BF for people with attenuated psychotic symptoms indicates that the intervention may hold potential if conducted per protocol. To reach this, longer training might be inevitable. Future studies are needed to further elucidate efficacy and applicability of HRV-BF in clinical samples.
Gesehen am 04.05.2020